2014
DOI: 10.4066/amj.2014.2211
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of self-directed learning (SDL) for teaching physiology to first-year medical students

Abstract: For first-year medical students, SDL is an effective teaching strategy for learning physiology. However, no additional benefit is gained by supplementing SDL with a lecture to facilitate learning physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 20 publications
3
33
1
Order By: Relevance
“…While these teaching approaches are aimed at supporting and assisting first year health science anatomy students to develop their knowledge and learning skills in anatomy, they also appear to produce more motivated and selfdirected learners. Our findings are consistent with previously reported self-directed learning approaches [7,8,12,13,15,18,21,23,24,26,27,29,31,[36][37][38]; however, the present study offers a greater variety of innovative, active teaching approaches that cover all four of the major sensory modalities for learning than those previously reported.…”
Section: Discussionsupporting
confidence: 94%
“…While these teaching approaches are aimed at supporting and assisting first year health science anatomy students to develop their knowledge and learning skills in anatomy, they also appear to produce more motivated and selfdirected learners. Our findings are consistent with previously reported self-directed learning approaches [7,8,12,13,15,18,21,23,24,26,27,29,31,[36][37][38]; however, the present study offers a greater variety of innovative, active teaching approaches that cover all four of the major sensory modalities for learning than those previously reported.…”
Section: Discussionsupporting
confidence: 94%
“…This is in contrast to many of the previous studies, which showed a significant advantage for SDL over didactic lectures. 17,18,19 In a study of self-directed learning in relation to anatomy, gross dissection at the Medical School of the University of Castilla-La Mancha, Spain, Mdel et al found that an objective-oriented self-learning approach provides maximal autonomy and independence in the achievement of objectives by the students in close association with academic staff. The data obtained from the study indicated that students engaged in self-directed learning through small groups working with faculty staff are able to self-improve their anatomical skills.…”
Section: Discussionmentioning
confidence: 99%
“…Kirtana et al in their study observed that self-directed learning is beneficial, especially in increasing knowledge about treating diseases and improving patient care. 15 They also observed that selfdirected learning has been benefited more for high scoring groups of medical students. The knowledge gained by both self-directed learning and interactive lectures were similar.…”
Section: Discussionmentioning
confidence: 97%